Automated Timetable Scheduling System For Direct Entry Student - Tuan Mohd Fakhruzzaman , Tuan Ismail (UTeM, 2008)
Automated timetable scheduling (ATSS) is an online system that is developed for FTMK management team for construct timetable for FTMK faculty. ATSS use the technology for making the timetable more easily, faster and systematic compare to manual system that are using now because it takes longer time only for construct the timetable. User of this system which is administrator, lecturer, dean, technician, student especially student direct intake will able to manage their timetable more manageable. User will be able to impose constraints on the schedule to encompass such irregularities such as the time constraint for certain lecturer, the software installed in certain lab and etc. weakness of the current system is not user friendly, and not flexible, wasting time and effort make the current system not more efficient anymore. Using RUP as methodology this system is using AJAX,PHP and MYSQL for client side which web and using Java for RMI.